1992
DOI: 10.1002/jsfa.2740580315
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of starch and non‐starch parameters to the eating quality of japanese white salted noodles

Abstract: : Viscograph paste viscosity parameters of starches isolated from 42 wheat varieties were highly correlated with each other and with measures of the quality of the derived Japanese white salted noodles. Better correlations with noodle quality were obtained when measurements o f wheat protein and grain hardness (PSI) as well as a starch viscosity parameter were included in the regression equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 5 publications
3
67
1
1
Order By: Relevance
“…With reduction in starch amylose content either by using partial waxy wheat flour or incorporation of waxy wheat flour, it may be possible to produce noodles, which require a reduced cooking time. The decrease in starch amylose content, however, may also accompany the decrease in firmness of cooked noodles (2,3,7,26) and increase in fat absorption of instant noodles (25).…”
Section: )mentioning
confidence: 98%
See 1 more Smart Citation
“…With reduction in starch amylose content either by using partial waxy wheat flour or incorporation of waxy wheat flour, it may be possible to produce noodles, which require a reduced cooking time. The decrease in starch amylose content, however, may also accompany the decrease in firmness of cooked noodles (2,3,7,26) and increase in fat absorption of instant noodles (25).…”
Section: )mentioning
confidence: 98%
“…Protein content and quality are significantly relatated with textural properties of cooked noodles (1)(2)(3)(4). High pasting viscosity, breakdown, and swelling power are desirable functional properties for the textural quality of white salted noodles (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 97%
“…Both protein quantity and quality influence the texture of white salted noodles. Starch is the main component of wheat flour and relationships have been reported between the starch properties and eating quality of white salted noodles (Oda et al 1980, Toyokawa et al 1989a, 1989b, Crosbie et al 1991, Konik et al 1992. Zhao et al (1998) reported that granule-bound starch synthase known as waxy protein, was related to the noodle quality.…”
Section: Introductionmentioning
confidence: 99%
“…High starch pasting peak viscosity (also referred to as "pasting") has been associated with superior udon noodle eating quality (Crosbie 1991;Konik et al 1992;Batey et al 1997). Udon noodles are usually produced using soft white wheat; however, Baik et al (1994a) determined that HW wheat with high peak viscosity and protein content between 9.5% and 11% can produce softer noodles than soft white wheat with relatively lower peak viscosities.…”
Section: Dual-purpose Hard White Wheatmentioning
confidence: 99%
“…Starch quality has a major impact on the end-use quality of HW wheat, especially on the eating properties of Japanese WSNs (Crosbie 1991;Konik et al 1992;Kruger 1996). Starch quality is evaluated by measuring a hot-pasting viscosity, as measured by the Rapid Visco Analyzer (RVA).…”
Section: Starch Qualitymentioning
confidence: 99%